2007
DOI: 10.1063/1.2730815
|View full text |Cite
|
Sign up to set email alerts
|

Exciton energy transfer between optically forbidden states of molecular aggregates

Abstract: 3-ethyl-2-[3-(3-ethyl-2(3H)-benzoxazolylidene)-1-propenyl]benzoxazolium iodide (dye I) and pseudoisocyanine bromide are employed to form H aggregates as donors and J aggregates as acceptors. The energy of an H band of the H aggregates is higher than that of a J band of the J aggregates. It was confirmed that excitation of the H band does not emit fluorescence by comparison of excitation spectra of dye I H aggregates with that of dye I monomer. Absorption, fluorescence, and excitation spectra of spin-coated fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…When exciton acceptors are embedded into the aggregate system, they can act as exciton trap sites that regulate the exciton diffusion (or migration) processes. [49][50][51][52][53] The insertion of quencher molecules (that exhibit lower energy than the donor molecules) into the molecular aggregates gives rise to a trapping of excitons, leading to a termination of the exciton migration, depending on the ratio between the luminescent energy donor and quenching acceptor moieties. In previous researches on squararine, 54,55 and oligophenylenevinylene dyes, [46][47][48] it was found that there are several factors which affect the trapping processes such as the relative concentration ratio of quencher and the overall aggregate structures.…”
Section: Formation Of Hetero-aggregates Incorporating Pbi Exciton Que...mentioning
confidence: 99%
“…When exciton acceptors are embedded into the aggregate system, they can act as exciton trap sites that regulate the exciton diffusion (or migration) processes. [49][50][51][52][53] The insertion of quencher molecules (that exhibit lower energy than the donor molecules) into the molecular aggregates gives rise to a trapping of excitons, leading to a termination of the exciton migration, depending on the ratio between the luminescent energy donor and quenching acceptor moieties. In previous researches on squararine, 54,55 and oligophenylenevinylene dyes, [46][47][48] it was found that there are several factors which affect the trapping processes such as the relative concentration ratio of quencher and the overall aggregate structures.…”
Section: Formation Of Hetero-aggregates Incorporating Pbi Exciton Que...mentioning
confidence: 99%
“…As a consequence, a photoexcited electron in H-aggregates assists J-aggregates to fluoresce. The modus operandi is an exciton energy transfer to optically forbidden, high-energy states . In a recent study, we have suggested that a reverse energy transfer mechanism from the allowed state of J-aggregates to the DOS of the dark states of H-aggregates is followed by electronic excitation to higher allowed bright states of the H-aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, even strictly optically forbidden H-aggregates can efficiently pass the excited-state energy to acceptors. 31 Therefore, the EnT efficiency of RhB-(BF 2 dbm) n polymers in solution should be related to the amount of long-lived excited-state aggregates present, 32 and should exponentially decrease with increasing temperature due to loss of aggregates. Meanwhile, RhB-(BF 2 dbm) n main chains are also likely to adapt more extended conformations at elevated temperatures, thus reducing the average donoracceptor distance.…”
Section: Resultsmentioning
confidence: 99%